The Analysis of Non-Verbal Information as a Determining Factor in Managerial Behaviour - E N Lobanova (RUDN journal of Sociology, 2013)
Non-verbal communication is studied in psychology. Being a part of human communication, though, it also contains useful information in terms of sociology of management. Different stages of business communication determine and are determined by non-verbal communication.